A critical look at the port area of rio de janeiro city (2010)
This paper aims to reflect on the position of mayor of Rio de Janeiro - over more than two decades - for the conservation of one of the city’s most traditional and historic areas: the port region. The area was characterized, from the beginning of the occupation of the town, in terms of uses and occupations considered ignoble, linked to the slave trade, housing the proletariat, manufacturing activities, port, among others. Over more than two decades have occurred since attempts were made to renew its urban texture and efforts were made to protect it, led by the local community and embraced by the Municipality. In both cases, in terms of conservation, the practical results were null, corroborating its traditional negative image. Nowadays, the area is expecting to undergo another attempt at conservation by the government, called “Porto Maravilha Project.” The initiative brings the unity of purpose of the three public tiers, proposing new forms of occupation of their land. However, it also notes the content of new proposals, a flagrant disregard for the traditional population and the lack of mechanisms for mitigating the inevitable and undesirable process of gentrification.